Peran Kegiatan Perayaan Gebyar Tahun Baru Islam di Masjid Al Hidayah dalam Memfasilitasi Pengembangan Kreativitas dan Kepercayaan Diri Anak-anak - Vitta Marta Bella; Deli Fadila; Irma Yani Agustin; Wahyu Zulfadli; Elsa Puspita Sari; Ismail Ismail (Lembaga Pengembangan Kinerja Dosen, 2024)
In the complex era of globalization, the development of children's creativity and confidence is an important aspect in addition to intellectual intelligence. This research aims to activate the effectiveness of the Islamic New Year Celebration activities held at the Al Hidayah Mosque, Bukit Pereviewuan 1 Village, Hamlet 5 in July 2024 in increasing the creativity and confidence of TPQ children. Involving around 60 participants, the activities included calligraphy competitions, adhan, Muslim fashion shows, and memorization of short letters. The research methods used are socialization, observation, and implementation of activities. The results of the study show that this activity significantly increases children's creativity through various competitions that allow innovative and innovative expression. In addition, this activity also succeeded in increasing the confidence of the participants, which can be seen from their bolder and enthusiastic attitude in participating. This activity contributes to the development of children's learning abilities and character, strengthening their foundation as individuals with integrity and competitiveness. Activities like this are expected to be carried out continuously to support the holistic development of children in a positive environment and full of religious values.